Crowdsourcing and Public Transportation: Barriers and Opportunities - Tatjana Apanasevic; Daniel Rudmark (International Telecommunications Society (ITS), 2021)
In the last decade, private companies have successfully used crowdsourcing to revolutionise mobility, while public transport companies are still mostly failing to utilise the benefits of crowdsourcing. The application of crowdsourcing in public transport is a new area of academic research, and research on crowdsourcing en route in real-time is missing. This research aims to address this gap, explore opportunities and challenges of this type of crowdsourcing, and conceptualise this phenomenon. The research is based on empirical data collected in five Northern European countries. Our research findings help identify areas where crowdsourcing en route can add value to public transport: new forms of communication, opportunities to communicate with third parties, and improved transit planning and optimisation. Identified challenges are related to behavioural change for users, a need to develop infrastructure to enable crowdsourcing en route, and financial rationalities.
Keywords: 330; Future of transportation; public transportation; emerging technologies; automated vehicles; crowdsourcing